CRISPR/Cas9 Methodology for the Generation of Knockout Deletions in Caenorhabditis elegans. Issue 1 (1st January 2019) - Au, Vinci; Li-Leger, Erica; Raymant, Greta; Flibotte, Stephane; Chen, George; Martin, Kiana; Fernando, Lisa; Doell, Claudia; Rosell, Federico I; Wang, Su; Edgley, Mark L; Rougvie, Ann E; et al.
Abstract: The Caenorhabditis elegans Gene Knockout Consortium is tasked with obtaining null mutations in each of the more than 20, 000 open reading frames (ORFs) of this organism. To date, approximately 15, 000 ORFs have associated putative null alleles. As there has been substantial success in using CRISPR/Cas9 in C. elegans, this appears to be the most promising technique to complete the task. To enhance the efficiency of using CRISPR/Cas9 to generate gene deletions in C. elegans we provide a web-based interface to access our database of guide RNAs (http://genome.sfu.ca/crispr ). When coupled with previously developed selection vectors, optimization for homology arm length, and the use of purified Cas9 protein, we demonstrate a robust and effective protocol for generating deletions for this large-scale project. Debate and speculation in the larger scientific community concerning off-target effects due to non-specific Cas9 cutting has prompted us to investigate through whole genome sequencing the occurrence of single nucleotide variants and indels accompanying targeted deletions. We did not detect any off-site variants above the natural spontaneous mutation rate and therefore conclude that this modified protocol does not generate off-target events to any significant degree in C. elegans . We did, however, observe a number of non-specific alterations at the target site itself following the Cas9-induced double-strand break and offer a protocol for best practice quality control for such events.